Experimental investigation on the enhancement of Mode I fracture toughness of adhesive bonded joints by electrospun nanofibers. Issue 11 (19th September 2018) - Musiari, F.; Pirondi, A.; Zucchelli, A.; Menozzi, D.; Belcari, J.; Brugo, T. M.; Zomparelli, L.
ABSTRACT: The use of an electrospun nylon nanofibrous mat at the interface between adjacent plies of a composite laminate is a promising mean to improve the delamination strength, as the nanomat acts a reinforcing web enabling a ply-to-ply bridging. This kind of reinforcement can be potentially used in other applications, such as adhesive bonding, where it may also work as adhesive carrier. The present work is therefore aimed at analysing the potential of an electrospun polymeric nanomat as adhesive carrier and reinforcing web in adhesive bonding. The adhesive is used to pre-impregnate a nylon nanofibrous mat that is then placed at the interface between two metal pieces and cured. The effectiveness of this procedure is evaluated by comparing of the mode-I fracture toughness measured 2024-T3 aluminum alloy DCB (Double Cantilever Beam) specimen bonded using a two-part epoxy resin with and without the nanomat.